An ethnography of the safety professional's dilemma: Safety work or the safety of work?. (August 2019) - Provan, David J.; Rae, Andrew J.; Dekker, Sidney W.A.
Highlights: Safety professionals focus on administrative, demonstrated and social safety work. Physical safety work is organisationally challenging for safety professionals. Safety professionals are often unable to articulate an objective for their tasks. Objectives of line management take priority over the advice of safety professionals. Safety professionals do not leverage safety science to inform their practice. Abstract: The safety profession has grown and evolved over recent decades, and despite the prominence of the role within organisations, there is limited research about the current state of safety professional practice. The objective of a safety professional's role is often stated as 'preventing incidents and harm to people', although the existing research fails to demonstrate a compelling link between safety professional practice and worker safety. More recently, a model of safety work in organisations proposed that safety activities fulfill broader social and political needs, in addition to the physical reduction of safety risk. In this paper, we report a study that investigated the underlying objectives of individual safety professional tasks, then performed thematic analysis to explore the contemporary role of safety professionals in organisations. 12 mid-level and senior-level safety professionals were interviewed at monthly intervals for six months regarding their work activities, in addition to an embedded researcher performing more than 240 h of field observations. Four categories of safety work in organisations – demonstrated, social, administrative, and physical – were used as priori themes to deductively analyze the data. The findings demonstrate strength of alignment between the safety professional role and line management, the increasing institutionalization of safety professional work, an absence of safety professional work directed at reducing safety risks to workers, and the lack of a clear connection between safety professional practice and safety science research.